Faktor-Faktor yang Mempengaruhi Partisipasi Masyarakat terhadap Minat Dalam Program Desa Sadar Jaminan Sosial Ketenagakerjaan pada Desa Amplas Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Nur Hayati Lubis; Yenni Samri Juliati Nasution; Annio Indah Lestari Nasution (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
.Employment social security is an innovative program that is given to the community in the village, integrating government programs. Cooperation with government officials through socialization and education to the working community in the village to better understand the benefits of the importance of social security. This study aims to determine the factors that influence the participation of the sandpaper village community towards interest in the employment social security awareness village program and the researchers took two factors, namely awareness and knowledge. The researcher wants to see the effect of awareness and knowledge on interest in the employment social security Desa Sadar program in Amplas Village, either partially or simultaneously. The method used in this research is quantitative. The population of this study was 2,625 people, so by using the Slovin formula the author got the number 96 which will be the sample in this study. Using primary data by distributing questionnaires and also distributing questionnaires directly to the Amplas Village community. Using multiple regression analysis method using hypothesis testing. The results of this study simultaneously from the variable awareness of knowledge and knowledge have a significant effect on interest in the social security awareness village program for employment. Then partially the awareness variable has no effect on interest and the knowledge variable itself has a significant effect on interest in the employment social security awareness village program. Keywords : Awareness, Interests, Knowledge and Desa Sadar Programs